The mediating role of employee ambidexterity and work engagement for talent management and medical representatives’ performance in Indonesian pharmaceutical companies - Muhammad Irfan Nasution; Imas Soemaryani; Yunizar; Hilmiana (Problems and Perspectives in Management, 2023)
The business success of pharmaceutical companies in achieving sales targets amid increasingly fierce market competition is highly dependent on the presence of a strong and efficient marketing team. This study aims to explore the impact of talent management on medical representatives’ performance in Indonesia, as well as to analyze the mediation role of employee ambidexterity and work engagement. This study used a quantitative approach involving 167 medical representatives as a sample. Data were collected through questionnaires distributed online and offline. The paper used structural equation modeling-partial least squares (SEM-PLS) for data analysis. The study’s results partially show that talent management, employee ambidexterity, and work engagement can significantly increase medical representatives’ performance (< 0.05). Furthermore, talent management significantly increases employee ambidexterity and work engagement (< 0.05). In addition, an indirect effect was found, where talent management can significantly improve medical representatives’ performance mediated by employee ambidexterity and work engagement (< 0.05). Employee ambidexterity can significantly increase medical representatives’ performance mediated by work engagement (< 0.05). These findings prove that talent management, employee ambidexterity, and work engagement are essential to improve medical representatives’ performance. In addition, these results also can develop more efficient marketing and human resource management strategies in the pharmaceutical industry in Indonesia.